Looking at the sun : - Fallows, James M. (Pantheon Books, 1994)
In a timely, even prophetic, portrait of Asia's rise and the magnitude of its challenge to the West, Fallows demolishes the myth that Japan is a capitalist country built on the Western model. He demonstrates instead how Japan's economic system treats business as an instrument of national interest while casting aside the traditional Western values of individual enterprise and human rights.